THE IMPACT OF INTERPERSONAL COMMUNICATION, A CREATIVE MINDSET, WORK ETHICS, AND JOB SATISFACTION ON THE PERFORMANCE OF JUNIOR HIGH SCHOOL TEACHERS IN LHOKSEUMAWE - Saiful Bahri; Benyamin Situmorang; Darwin Darwin (Jurnal As-Salam, 2022)
This study seeks to learn about: (1) Innovative work ethic attitudes, (2) Interpersonal interactions about work ethics, (3) A creative approach to job satisfaction (4) Personal interactions that contribute to job satisfaction. 5) The impact of a creative mindset, effective interpersonal communication, a strong work ethic, and job happiness on teachers' effectiveness. Using quantitative methods, a survey approach, a population of 584 teachers, a sample of 237 teachers, a proportional random sampling technique based on the provisions of the model by Slovin, a questionnaire data collection technique called the "Likert scale," and plans for path analysis data processing, this research was carried out at public junior high schools in Lhokseumawe. The direct effect of innovation on work ethic is 0.048; the direct influence of interpersonal communication on work ethic is 0.05; the immediate impact of innovation on job satisfaction is 0.019; the direct impact of interpersonal communication on job satisfaction is 0.04; the direct effect of innovation on teacher performance is 0.22; the direct influence of interpersonal communication on performance is 0.04; these are just a few of the research findings. Concurrent research findings A total of 0.53 of the characteristics that directly affect teacher performance are innovative attitude, interpersonal communication, work ethic, and job satisfaction; the remaining 0.47 is affected by other factors.